2009
DOI: 10.1002/jsc.850
|View full text |Cite
|
Sign up to set email alerts
|

A capital partnership: how human and venture capital affect the growth of high‐tech start‐ups

Abstract: ᭹ Founders' human capital and venture capital (VC) are two fundamental ingredients for new venture success in high-tech sectors. We jointly investigate their infl uence on the growth performance of a large sample of Italian high-tech start-ups and fi nd:-the importance of both components; -some characteristics of founders' human capital also exert an indirect rather than a direct effect on growth by attracting VC; -the 'coach' function performed by Italian venture capitalists on invested companies is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Accelerators play an important role in facilitating connections between firms and sources of entrepreneurial finance (OECD, 2013). Access to venture capital (VC), in particular, is seen as critical for the successful development of high performing ventures (Lerner, 2010), as some play an important role in mentoring businesses, providing them with contacts and enabling them to connect with customers (Colombo and Grilli, 2009). This is the kind of 'smart' money brings with it an array of ancillary benefits which positively benefit a firm.…”
Section: Programme Interventionsmentioning
confidence: 99%
“…Accelerators play an important role in facilitating connections between firms and sources of entrepreneurial finance (OECD, 2013). Access to venture capital (VC), in particular, is seen as critical for the successful development of high performing ventures (Lerner, 2010), as some play an important role in mentoring businesses, providing them with contacts and enabling them to connect with customers (Colombo and Grilli, 2009). This is the kind of 'smart' money brings with it an array of ancillary benefits which positively benefit a firm.…”
Section: Programme Interventionsmentioning
confidence: 99%
“…VC is a possible solution to this problem (Colombo and Grilli, 2009). VC financing provides startups with resources and opportunities to innovate with new business models.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that companies that have workers with high levels of human capital can incorporate their production process more easily in emerging technologies to withdraw maximum efficiency. This situation is confirmed by Alvarez and Rodriguez (2011) and Colombo and Grilli (2009) who argued that several dimensions of human capital such as the entrepreneurs' level of formal education, training, and social networks are the determining factors in the sustainability and growth of companies in the market. Furthermore, human capital in companies can boost the development of research and development (R&D) activities by driving the creation of new products (Bodman & Le, 2013).…”
Section: Exploring the Role Of Education On The Entrepreneurial Motivmentioning
confidence: 70%
“…Although academic spin-offs are mostly entrepreneurs with high academic qualifications, the role and relevance assumed by the founder's education are not unanimous. Various studies revealed the relationship between entrepreneurial motivations and education levels, indicating that high qualification levels of entrepreneurs contributed to the establishment of new academic spin-offs (Colombo & Grilli, 2009;Gimmon & Levie, 2010). However, the findings by Teixeira and Castro (2015) suggested that high levels of education and existence of complementary technical education were statistically non-significant for the establishment of university spin-offs.…”
Section: Exploring the Role Of Education On The Entrepreneurial Motivmentioning
confidence: 99%